Antigen-Specific Gene Therapy after Immunisation Reduces the Severity of Collagen-Induced Arthritis - Tove Eneljung; Sara Tengvall; Pernilla Jirholt; Louise Henningsson; Rikard Holmdahl; Kenth Gustafsson; Inger Gjertsson (Clinical and Developmental Immunology)
Reestablishment of tolerance induction in rheumatoid arthritis (RA) would be an optimal treatment with few, if any, side effects. However, to develop such a treatment further insights in the immunological mechanisms governing tolerance are needed. We have developed a model of antigen-specific tolerance in collagen type II (CII) induced arthritis (CIA) using lentivirus-based gene therapy. The immunodominant epitope of CII was inserted into a lentivirus vector to achieve expression on the MHC class II molecule and the lentiviral particles were subsequently intravenously injected at different time points during CIA. Injection of lentiviral particles in early phases of CIA, that is, at day 7 or day 26 after CII immunisation, partially prevented development of arthritis, decreased the serum levels of CII-specific IgG antibodies, and enhanced the suppressive function of CII-specific T regulatory cells. When lentiviral particles were injected during manifest arthritis, that is, at day 31 after CII immunisation, the severity of arthritis progression was ameliorated, the levels of CII-specific IgG antibodies decreased and the proportion of T regulatory cells increased. Thus, antigen-specific gene therapy is effective when administered throughout the inflammatory course of arthritis and offers a good model for investigation of the basic mechanisms during tolerance in CIA.